Role of community health volunteers in identifying people with elevated blood pressure for diagnosis and monitoring of hypertension in Malawi: a qualitative study - Safary, Elvis; Mwandeti, Micrina; Matanje, Beatrice; Beiersmann, Claudia; Mtaita, Caroline; Shiroya, Veronica; Winkler, Volker; Deckert, Andreas; Kumar, Pratap; Phiri, Sam; Neuhann, Florian (BMC cardiovascular disorders, 2021)
In recent years, there has been greater recognition of the important role of community health volunteers in many countries and their important role informs many health programs. This include health education, provision of services such as screening, monitoring and referral to health facilities. Their roles are better understood in the areas of communicable diseases like HIV infection, Tuberculosis and Malaria however little is known about their role in non-communicable diseases. This study seeks to explore perception of CHVs’ functions, tasks, and their fulfilment in identifying people with elevated blood pressure for diagnosis and monitoring of hypertension in Lilongwe, Malawi.
Gesehen am 07.10.2021